PENGGUNAAN MEDIA KOMUNIKASI DIGITAL DALAM MEMPROMOSIKAN BRAND IMAGE DI YAYASAN PANTI ASUHAN YATIM PIATU DAN DHUAFA MAKTABUL AITAM TANGERANG - Katry Anggraini; Sewaka Sewaka; Firman Amir (Universiitas Pamulang, 2023)
ABSTRACT In the last decade, digital communication media has been frequently used by marketers in addition to selling products, as well as building brands. Digital marketing that is carried out by many companies or organizations turns out to have a big impact in increasing brand awareness of the products or services they sell. In carrying out a digital marketing strategy, it is required to be creative in marketing products. It is intended that the products being marketed can be easily remembered by the market. Advances in information technology that are all digital like now, where communication is done online. The content of the message is very important. The more message content an organization or company has, the easier it will be for someone to find products or services offered by the organization or company. Effective message content is valuable, relevant and optimal message content that is published consistently across platforms. To create or formulate an effective message, marketers need to understand several things, namely the message must combine the core brand, values, and principles of the whole company or organization, the message must be aligned with the fundamental goals, and the message needs to be adapted to the target audience and the channels or media used. . Social media is one of the digital communication media that has a large number of active users in Indonesia. In addition, currently social media is also used as a medium of online marketing communication. Through digital communication media, online businesses can easily market their products by uploading photos or videos about the products or services being sold. Utilizing digital communication media, business people can strengthen their brand image to the public. Community Service (PKM) is carried out by providing counseling so that information can be channeled to foundation staff and from several Community Service results (PKM) related to education on the use of digital communication media in terms of promoting brand image. The results obtained in this extension education are technology-based marketing techniques by utilizing digital communication media. Digital communication media is an effective marketing tool because social media is a means of communication that is widely used by society today. Keywords: Digital Communication Media, Promotion, and Brand Image